The autophagy-enhancing drug carbamazepine improves neuropathology and motor impairment in mouse models of Machado-Joseph disease - Vasconcelos-Ferreira, Ana (2021)
Machado-Joseph disease (MJD), or spinocerebellar ataxia type 3 (SCA3), is the most common autosomal dominantly-inherited ataxia worldwide and is characterised by the accumulation of mutant ataxin-3 (mutATXN3) in different brain regions, leading to neurodegeneration. Currently, there are no available treatments able to block disease progression. In this study, we investigated whether carbamazepine (CBZ) would activate autophagy and mitigate MJD pathology.